Nos Ventos de Bará: Um estudo sobre as personagens no primeiro romance de Miriam Alves - Vieira, Andressa Santos (2024)
This doctoral research aimed to expand the studies initiated in the Master's program through the short stories of Mulher Mat(r)iz (2011), focusing on the black characters created by Miriam Aparecida Alves, thereby contributing to Alves's critical theoretical collection. For this reason we decided, in this new phase of research, to emphasize the appreciation of a fictional narrative by selecting her first romance, Bará na trilha do vento, published in 2015 by Ogum’s Toques Negros. The current proposal is justified by the need to develop a theoretical and critical perspective on Alves's work, an author of great importance for national literary production and, particularly, for Literatura negra brasileira. Thus, this study aims to contribute to the enhancement of the critical fortune surrounding Miriam Alves and to promote a more attentive look at her work and the construction of her characters. Our hypothesis is that the writer presents, through the romance "Bará na trilha do vento" (2015), black characters as human subjects rather than mere objects for domination, stereotyping, and dehumanization perpetuated by whiteness. In this regard, we believe that the narrative (re)writes the place and images for black bodies, bringing them out of the shadows of silencing and relocating them beyond stereotypes, stigmas, and social margins. By addressing necessary issues such as loneliness, violence, and racism through the characters, the romance challenges and promotes the formation of new images and identities for black bodies in literature.